THE EFFECT OF FINANCIAL PERFORMANCE ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE (AN EMPIRICAL STUDY OF BANKS LISTED ON THE INDONESIA STOCK EXCHANGE) - Munira Ulfa; Nurlela; Husaini; Zulfan (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to examine the effect of financial performance on Corporate Social Responsibility (CSR) disclosure (an empirical study on banks listed on the Indonesia Stock Exchange). Financial performance is measured using leverage, return on assets, and company age. The data used in this study are secondary data from banks listed on the Indonesia Stock Exchange during the 2019-2023 period. The method used to analyze the relationship between the independent and dependent variables is panel data regression analysis, assisted by EViews software. The results show that, partially, the Debt to Equity Ratio has a significant and positive effect on CSR disclosure; Return on Assets also has a significant and positive effect; and Company Age has a significant and positive effect on CSR disclosure in banks listed on the Indonesia Stock Exchange in 2019-2023.